Pharmacokinetics and safety of early nevirapine-based antiretroviral therapy for neonates at high risk for perinatal HIV infection: a phase 1/2 proof of concept study. Issue 3 (March 2021) - Ruel, Theodore D; Capparelli, Edmund V; Tierney, Camlin; Nelson, Bryan S; Coletti, Anne; Bryson, Yvonne; Cotton, Mark F; Spector, Stephen A; Mirochnick, Mark; LeBlanc, Rebecca; Reding, Christina; Zimmer, Bonnie; et al.
Summary: Background: With increasing intention to treat HIV as early as possible, evidence to confirm the safety and therapeutic drug concentrations of a nevirapine-based antiretroviral regimen in the early neonatal period is needed. This study aims to establish dosing of nevirapine for very early treatment of HIV-exposed neonates at high risk of HIV acquisition. Methods: IMPAACT P1115 is a multinational phase 1/2 proof-of-concept study in which presumptive treatment for in-utero HIV infection is initiated within 48 h of birth in HIV-exposed neonates at high risk of HIV acquisition. Participants were neonates who were at least 34 weeks gestational age at birth and enrolled within 48 h of birth, born to women with presumed or confirmed HIV infection who had not received antiretrovirals during this pregnancy. The regimen consisted of two nucleoside reverse transcriptase inhibitors plus nevirapine dosed at 6 mg/kg twice daily for term neonates (≥37 weeks gestational age) or 4 mg/kg twice daily for 1 week and 6 mg/kg twice daily thereafter for preterm neonates (34 to <37 weeks gestational age). Here, we report the secondary outcomes of the study: nevirapine exposures in study weeks 1 and 2 and treatment-associated grade 3 or 4 adverse events at least possibly related to study treatment up to study week 4. A population pharmacokinetic model to assess nevirapine exposure was developed from dried blood spot and plasma nevirapine concentrations at study weeks 1 and 2. Nevirapine exposure was assessed in all patients with available blood samples and safety was assessed in all participants. This trial is registered at ClinicalTrials.gov (NCT02140255 ). Findings: Between Jan 23, 2015, and Sept 4, 2017, 438 neonates were enrolled and included in analyses; 36 had in-utero HIV infection and 389 (89%) were born at term. Neonates without confirmed in-utero HIV infection received nevirapine for a median of 13 days (IQR 7–14). Measured dried blood spot nevirapine concentrations were higher than the minimum HIV treatment target (3 μg/mL) in 314 (90%, 95% CI 86–93) of 349 neonates at week 1 and 174 (87%, 81–91) of 201 at week 2. In Monte-Carlo simulations, week 1 nevirapine concentrations exceeded 3 μg/mL in 80% of term neonates and 82% of preterm neonates. DAIDS grade 3 or 4 adverse events at least possibly related to antiretrovirals occurred in 30 (7%, 95% CI 5–10) of 438 infants but did not lead to nevirapine cessation in any neonates; neutropenia (25 [6%] neonates) and anaemia (six [1%]) were most common. Interpretation: Nevirapine at the dose studied was confirmed to be safe and provides therapeutic exposure concentrations. These data support nevirapine as a component of presumptive HIV treatment in high-risk neonates. Funding: National Institute of Allergy and Infectious Diseases, Eunice Kennedy Shriver National Institute of Child Health and Human Development, and the National Institute of Mental Health.